2004
DOI: 10.1001/jama.291.4.442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Breast Augmentation on the Accuracy of Mammography and Cancer Characteristics

Abstract: REAST AUGMENTATION IS THE third most common type of plastic surgery performed for cosmetic reasons in the United States, with 268 888 procedures in 2002. 1 In 2 studies conducted in the late 1980s, between 3.3 and 8.1 per 1000 women reported ever having breast implants. 2,3 Although breast implants have not been found to be associated with an increased risk of breast cancer, 4,5 implants may interfere with routine mammography evaluation; therefore, women with breast augmentation may be more likely to be diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(69 citation statements)
references
References 43 publications
2
60
1
6
Order By: Relevance
“…An implant shows up as a solid white orb on a mammogram, which can hide tumours above or below the implant. 9 Specially trained technicians can partially compensate by taking additional views of the implanted breast, but additional views generally cost more, take more time, and expose the woman to more radiation. Since most women wanting breast implants plan to have them for the rest of their lives, it is important to stress this issue to women of all ages before they make a decision about getting breast implants.…”
Section: Risk Of Reduced Accuracy Of Mammogramsmentioning
confidence: 99%
“…An implant shows up as a solid white orb on a mammogram, which can hide tumours above or below the implant. 9 Specially trained technicians can partially compensate by taking additional views of the implanted breast, but additional views generally cost more, take more time, and expose the woman to more radiation. Since most women wanting breast implants plan to have them for the rest of their lives, it is important to stress this issue to women of all ages before they make a decision about getting breast implants.…”
Section: Risk Of Reduced Accuracy Of Mammogramsmentioning
confidence: 99%
“…In addition to our previous report, 2 publications by Silverstein and colleagues reported that breast implant women presented with more advanced stage at breast cancer diagnosis when compared with nonaugmented women (19,20). Although not statistically significant, several studies showed a tendency toward advanced breast tumors at diagnosis for women who received augmentation mammaplasty (6,(29)(30)(31)(32)(33)(34)(35). However, several other publications found little or no evidence that implant women were diagnosed at a later stage (9,12,(22)(23)(24)(25)(26)(27)(28)57).…”
Section: Principal Findings and Comparison With Previous Studiesmentioning
confidence: 50%
“…Only 3 publications, including our previous report, showed a statistically significant shift toward more advanced breast tumors at diagnosis among augmented women (19)(20)(21). However, several other publications reported no statistically significant differences in breast cancer stage at diagnosis comparing augmented to nonaugmented women (6,9,12,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Furthermore, specific implant characteristics such as implant volume and placement might affect the detection of breast cancer (36).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Women were classified on the basis of demographic and clinical covariates known to be associated with the accuracy of mammography, 17,22,23 including age (in 5-year categories), breast density, and months since the most recent mammography. Facilities were classified according to academic affiliation, relative frequencies of screening and diagnostic imaging, interpretation of screening mammograms in batches of 10 or more, availability of interventional services (e.g., core biopsy), number of radiologists who specialized in breast imaging, interpretation of screening mammograms by more than one radiologist (i.e., double-reading), and the frequency of feedback about performance and the method used to review it.…”
Section: Performance Measures and Data Classificationmentioning
confidence: 99%